Levelized Cost of Energy (LCOE) of Different Photovoltaic Technologies - Maria Cristea; Ciprian Cristea; Radu-Adrian Tîrnovan; Florica Mioara Șerban (Applied Sciences)
Renewable energy sources are critical to the global effort to achieve carbon neutrality. Alongside hydropower, wind and nuclear plants, the photovoltaic (PV) systems developed greatly, with new PV technologies emerging in recent years. Although the conversion efficiencies are improving and the materials used have a lower impact on the environment, the feasibility of these technologies is required to be assessed. This paper proposes a levelized cost of energy (LCOE) model to assess the feasibility of five PV technologies: high-efficiency silicon heterojunction cells (HJT), N-type monocrystalline silicon cells (N-type), P-type passivated emitter and rear contact cells (PERC), N-type tunnel oxide passivated contact cells (TOPCon) and bifacial TOPCon. The LCOE considers capital investment, government incentives, operation and maintenance costs, residual value of PV modules and total energy output during the PV system’s life span. To determine the influence of PV system’s capacity over the LCOE values, three systems are analyzed for each technology: 3 kW, 5 kW and 7 kW. The results show that the largest PV systems have the lowest LCOE values, ranging from 2.39 c€/kWh (TOPCon) to 2.92 c€/kWh (HJT) when incentives are accessed, and ranging from 6.05 c€/kWh (TOPCon) to 6.51 c€/kWh (HJT) without subsidies. The 3 kW and 5 kW PV systems have higher LCOE values due to lower energy output during lifetime.